2008
DOI: 10.1101/gad.1692808
|View full text |Cite
|
Sign up to set email alerts
|

A functional link between Wnt signaling and SKP2-independent p27 turnover in mammary tumors

Abstract: Loss of the CDK inhibitor p27KIP1 is widely linked with poor prognosis in human cancer. In Wnt10b-expressing mammary tumors, levels of p27 KIP1 were extremely low; conversely, Wnt10b-null mammary cells expressed high levels of this protein, suggesting Wnt-dependent regulation of p27 KIP1 . Interestingly we found that Wnt-induced turnover of p27 KIP1 was independent from classical SCF SKP2 -mediated degradation in both mouse and human cells. Instead, turnover required Cullin 4A and Cullin 4B, components of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 42 publications
(62 reference statements)
1
82
1
2
Order By: Relevance
“…Furthermore, we found an inverse relation of mRNA level of the cyclin-dependent kinase inhibitor p27 KIP1 and the amount of cytoplasmatic ßCat (Table II), indicating that the expression of p27(KIP1) could be controlled by Wnt in BTC cells. The p27 protein has been described as a negative Wnt target (39,40). For the mRNA level of Wnt receptors or transcription factors we could not find similar correlations (Tables II and III).…”
Section: Effects Of Wnt Pathway Inhibitioncontrasting
confidence: 35%
“…Furthermore, we found an inverse relation of mRNA level of the cyclin-dependent kinase inhibitor p27 KIP1 and the amount of cytoplasmatic ßCat (Table II), indicating that the expression of p27(KIP1) could be controlled by Wnt in BTC cells. The p27 protein has been described as a negative Wnt target (39,40). For the mRNA level of Wnt receptors or transcription factors we could not find similar correlations (Tables II and III).…”
Section: Effects Of Wnt Pathway Inhibitioncontrasting
confidence: 35%
“…Previously, Lim et al demonstrated p27 degradative function of Skp2 in low-grade lymphomas but not in aggressive lymphomas (33), which suggests that other factors contribute to deregulation of p27 expression in these tumors. It has been reported that Wnt-induced turnover of p27 was independent from classical SCF Skp2 -mediated degradation in which both Cul4A and Cul4B, components of an alternative E3 ubiquitin ligase, were required for Wnt-induced p27 degradation and S-phase progression (34).…”
Section: Discussionmentioning
confidence: 99%
“…these pathways could be modified by extracellular signaling molecules and operate redundantly in order to regulate cell cycle progression and maintenance of genomic integrity. 50,51 …”
Section: Conditional Inactivation Of Geminin In the Mouse Immune Systemmentioning
confidence: 99%